Capacity - Kyle Bagwell; Garey Ramey (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1990)
We show that when avoidable fixed costs are introduced into the capacity-and-entry model of Dixit(1980) and Ware(1984), there arises a coordination problem in selecting among postentry Nash equilibria. Elimination of weakly dominated strategies makes it possible for the entrant to us a market-capturing strategy, consisting of a large capacity commitment that selects the entrant's preferred postentry equilibrium and drives the incumbent from the market. Deterring the entrant's market-capturing strategy typically requires the incumbent to reduce its initial capacity choice. As avoidable fixed costs rise, the incumben must restrict its capacity by a greater amount, and the relative advantage of the entrant rises.
Keywords: 330